Idea Europa. - Bruni, Valeria; Magazzini del Sale, Siena; Galleria Civica Piazza Cavbour, Padova ([S.l.] : Contemporanea Editrice, 1994)
Akkerman, Philip ; Bardenheuer, Herbert ; Bouronikos, Christos ; Brogi, Giorgio ; Canevari, Paolo ; Cullen, Shane ; D.C., Franky ; De Leon, Jose ; Hannemann, Mette ; Krian, Erich ; Innes, Callum ; Lemmerz, Christian ; Manche, Matthieu ; Mulders, Marc ; Ni Chiosain, Fionnuala ; Perrin, Philippe ; Rego, Domingos ; Roda, Fernand ; Rojas, Antonio ; Sander, Doris ; Teixeira, Inez ; Theodoulos ; Tuymans, Luc ; Wallinger, Mark
Idea Europa, Magazzini del Sale, Siena, 21 Ottobre - 20 Novembre 1994 ; Galleria Civica Piazza Cavbour, Padova, 24 Dicembre 1994 - 29 Gennaio 1995
boek